2021
DOI: 10.1002/jgm.3382
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the long non‐coding RNA UNC5B‐AS1/miR‐4455/RSPO4 axis reduces cervical cancer growth in vitro and in vivo

Abstract: Background: Long non-coding RNAs (lncRNAs) are significant regulatory factors for the initiation and development of numerous malignant tumors, including cervical cancer (CC). The expression of lncRNA unc-5 netrin receptor B antisense RNA 1 (UNC5B-AS1, also known as UASR1) is up-regulated in tissues of cervical squamous cell carcinoma and endocervical adenocarcinoma compared to in normal tissues based on the GEPIA database. In the present study, we explored the functions of UNC5B-AS1 and its underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The UNC5B-AS1 functions similarly to FOXD2-AS1, and its expression is up-regulated in hepatocellular carcinoma, papillary thyroid cancer, and prostate cancer [ 58 – 60 ]. The silencing of UNC5B-AS1 inhibits tumor growth [ 61 , 62 ], but it has not been reported in osteosarcoma. SENCR has been extensively studied in the vascular smooth muscle cells and endothelial cells [ 63 , 64 ], but recent studies have showed that it also has a role in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The UNC5B-AS1 functions similarly to FOXD2-AS1, and its expression is up-regulated in hepatocellular carcinoma, papillary thyroid cancer, and prostate cancer [ 58 – 60 ]. The silencing of UNC5B-AS1 inhibits tumor growth [ 61 , 62 ], but it has not been reported in osteosarcoma. SENCR has been extensively studied in the vascular smooth muscle cells and endothelial cells [ 63 , 64 ], but recent studies have showed that it also has a role in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…UNC5B-AS1 , also known as UASR1 , was found to be downregulated in senescent normal oral keratinocytes, [ 47 ]. In contrast, UNC5B-AS1 upregulation increased cell proliferation in breast, cervical, colorectal, oral squamous cell, and papillary thyroid cancers [ 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA-29c inhibits the epithelial-mesenchymal transition in cervical cancer cells, leading to the inhibition of proliferation, invasion and metastasis [74]. The inhibition of the microRNA-4455 axis expression reduces cervical cancer growth in vitro and in vivo [75]. Thus, it appears that calcitriol-dependent increased bioavailability of DDX5 might cause the RNA substrates to be readily processed by the ribonuclease Dicer, enhancing in this way the maturation rate of microRNAs associated with anti-cancer-related functions.…”
Section: The Vitamin D Endocrine System In Cervical Cancer: Preclinic...mentioning
confidence: 99%